The novel inhibitor PRI-724 for Wnt/β-catenin/CBP signaling ameliorates bleomycin-induced pulmonary fibrosis in mice. (9th August 2019) - Okazaki, Hiroyasu; Sato, Seidai; Koyama, Kazuya; Morizumi, Shun; Abe, Shuichi; Azuma, Momoyo; Chen, Yajuan; Goto, Hisatsugu; Aono, Yoshinori; Ogawa, Hirohisa; Kagawa, Kozo; Nishimura, Haruka; et al.
Abstract: Purpose/Aim of the Study: Wnt/β-catenin signaling was reported to be activated in pulmonary fibrosis, and was focused on as a target for antifibrotic therapy. However, the mechanism how the inhibition of Wnt/β-catenin signaling ameliorate pulmonary fibrosis has not been fully elucidated. The purpose of this study is to explore the target cells of Wnt/β-catenin inhibition in pulmonary fibrosis and to examine the antifibrotic effect of the novel inhibitor PRI-724 specifically disrupting the interaction of β-catenin and CBP. Materials and Methods: The effect of C-82, an active metabolite of PRI-724, on the expression of TGF-β1 and α-smooth muscle actin (SMA) was examined on fibroblasts and macrophages. We also examined the effects of PRI-724 in mouse model of bleomycin-induced pulmonary fibrosis. Results: The activation and increased accumulation of β-catenin in the canonical pathway were detected in lung fibroblasts as well as macrophages stimulated by Wnt3a using Western blotting. Treatment with C-82 reduced CBP protein and increased p300 protein binding to β-catenin in the nucleus of lung fibroblasts. In addition, C-82 inhibited the expression of SMA in lung fibroblasts treated with TGF-β, indicating the inhibition of myofibroblast differentiation. In the fibrotic lungs induced by bleomycin, β-catenin was stained strongly in macrophages, but the staining of β-catenin in alveolar epithelial cells and fibroblasts was weak. The administration of PRI-724 ameliorated pulmonary fibrosis induced by bleomycin in mice when administered with a late, but not an early, treatment schedule. Analysis of bronchoalveolar fluid (BALF) showed a decreased number of alveolar macrophages. In addition, the level of TGF-β1 in BALF was decreased in mice treated with PRI-724. C-82 also inhibited the production of TGF-β1 by alveolar macrophages. Conclusions: These results suggest that the β-catenin/CBP inhibitor PRI-724 is a potent antifibrotic agent that acts by modulating the activity of macrophages in the lungs.